2016
DOI: 10.1021/acs.jchemed.6b00546
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Effect of Surfactant on Water Retention of Waxy Leaf Surfaces

Abstract: We report here the development of an inexpensive and engaging laboratory-based activity that can help students learn about the scientific method and the role of plant epicuticular waxes and surfactant function on waxy plant leaves as real life example in the agricultural industry. Three each of nontreated collard leaves (Brassica oleraceae L. Acephala group) and brushed-leaves were sprayed with water to demonstrate hydrophobicity of epicuticular waxes. Another set of three nontreated collard leaves was sprayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
(46 reference statements)
1
17
0
Order By: Relevance
“…A majority of respondents agreed or strongly agreed with the statements “I can utilize a smartphone or smart device to collect data for plant science experiment.” (88.0%) and “I enjoyed using my smartphone or smart device when completing this experiment” (72.0%). This result corresponds with previous findings that students are comfortable and enjoy using their smartphones in the laboratory environment as an educational tool . Respondents also agreed they “…can conduct inferential statistics” (74.7%).…”
Section: Surveysupporting
confidence: 88%
See 2 more Smart Citations
“…A majority of respondents agreed or strongly agreed with the statements “I can utilize a smartphone or smart device to collect data for plant science experiment.” (88.0%) and “I enjoyed using my smartphone or smart device when completing this experiment” (72.0%). This result corresponds with previous findings that students are comfortable and enjoy using their smartphones in the laboratory environment as an educational tool . Respondents also agreed they “…can conduct inferential statistics” (74.7%).…”
Section: Surveysupporting
confidence: 88%
“…(88.0%) and "I enjoyed using my smartphone or smart device when completing this experiment" (72.0%). This result corresponds with previous findings that students are comfortable and enjoy using their smartphones in the laboratory environment as an educational tool [15]. Respondents also agreed they "…can conduct inferential statistics" (74.7%).…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the efficacy of the laboratory activity, we appended a Likert survey (Table 1) to the lab handout and asked that students complete it along with answering lab discussion questions that were due the following week. Methods for the survey were modified from Turk (2016) and Chiu et al (2016). The goal of the survey was to evaluate the success of the module in achieving the three learning objectives noted above.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, smartphones are promising tools for use in field analysis in remote regions and developing countries. , In education research, there have been numerous reports using smartphone cameras in chemical analysis. Some examples include for titration end-point determination, , in colorimetric studies of chemical kinetics, for measuring contact angle, for paper-based colorimetric microfluidic devices, and as a detector component in 3D printed spectrophotometers. , Kuntzleman et al and Knutson and Jacobson have shown that RGB image analysis of chromophore-containing samples photographed with an irradiant background (in their examples, colored and white PowerPoint slides, respectively) can be used as a visible-light spectrophotometer. , In this example, spectral analysis is limited to red, green, and blue channelsthus, the method presumably works best with chromophores that absorb purely red, green, or blue wavelengths. Given that most college students have access to or possess a smartphone or digital camera, colorimetric and absorbance-based smartphone analyses are well-suited for chemistry experimentation at home.…”
Section: Introductionmentioning
confidence: 99%